AN ANALYSIS OF THE FACTOR OF SPEAKING ANXIETY OF THE TENTH GRADE STUDENTS AT SMAN 1 TEMBILAHAN - Nurfadilla; Edi Ardian; Sri Erma Purwanti (Program Studi Pendidikan Bahasa Inggris, 2024)
The phenomenon of anxious students often occure in the process of learning English, especially in class. Where students feel scared and embarrassed when speaking English. The purpose of this study was to determine the extent of the factor of students anxiety level when speaking english at SMAN 1 Tembilahan. This research design is the descriptive quantitative and the research instrument is questionnaire, containing 10 statements, and the total population was 313 people, and the sampling technique in this study is the purposive sampling which was the students of class X-9 at SMAN 1 Tembilahan. Based on the result of calculating student responses to 10 questionnaire statements, There were several factors that make students got speaking anxiety, such as the learner beliefs about language learning where it is placed 212,5 of amount, that it was in very high position, the next factor is Instructor beliefs about language teaching where it is placed 137 of amount, that is was in high position and the next factor is personal and interpersonal anxieties, classroom procedures, and language testing where it is placed 107,2, 104,5, and 110 of amount, that is was in average position. The result indicate that student’s speaking anxiety of the Tenth Grade Students at SMAN 1 Tembilahan was 134,3. Based on the result of the research that student’s speaking anxiety of the tenth grade students at SMAN 1 Tembilahan is in categorized high level. Based on this analysis, it was conclude that the level of students' anxiety was still unable to manage their own speaking anxiety.